Implementation of the Sorogan Method in Enhancing the Reading Skills of Kitab Kuning at Pondok Pesantren - Masrifatin, Yuni; Rahmania, Nurani; Lela, Kamila Wahdah Noor (IERA, Islamic Education and Research Academy, 2023)
This research aims to explain the application of the yellow book sorogan method, explain the supporting and inhibiting factors of the yellow book sorogan method, and explain the influence of the sorogan method on improving yellow book reading skills. This research uses a qualitative descriptive approach with case studies. Data collection techniques include observation, interviews and documentation. The following are the results of this research, the supporting factors in sorogan activities are the seniors and administrators who help carry out the sorogan activities and the availability of adequate infrastructure and the inhibiting factor is the lack of preparation before the sorogan activities begin. The impact of the sorogan yellow book is that students who previously could not read at all can now read and understand the yellow book according to its rules and train students' sense of responsibility and self-awareness